2015
DOI: 10.1016/j.addr.2015.02.008
|View full text |Cite
|
Sign up to set email alerts
|

Delivery of therapeutic oligonucleotides with cell penetrating peptides

Abstract: Oligonucleotide-based drugs have received considerable attention for their capacity to modulate gene expression very specifically and as a consequence they have found applications in the treatment of many human acquired or genetic diseases. Clinical translation has been often hampered by poor biodistribution, however. Cell-penetrating peptides (CPPs) appear as a possibility to increase the cellular delivery of non-permeant biomolecules such as nucleic acids. This review focuses on CPP-delivery of several class… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
154
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 224 publications
(155 citation statements)
references
References 183 publications
(261 reference statements)
0
154
0
1
Order By: Relevance
“…PMOs are chemically modified ONs that harbor a morpholino moiety instead of the ribose moiety and phosphorodiamidate linkages instead of the phosphodiester linkages. CPP conjugation to PMO has been performed via a variety of methods including: maleimide linkage, disulfide linkage, click chemistry, or amide linkage between the free PMO secondary amine and an activated carboxylic group at the c-terminus of the peptide, which is the most popular [21]. Initial reports showing promising results using this chemistry were based on using arginine-rich peptides together with other chemical modifications such as aminohexanoic acid and beta alanine [44,45].…”
Section: Covalent Conjugation Approach For Nucleic Acid Delivery Withmentioning
confidence: 98%
See 1 more Smart Citation
“…PMOs are chemically modified ONs that harbor a morpholino moiety instead of the ribose moiety and phosphorodiamidate linkages instead of the phosphodiester linkages. CPP conjugation to PMO has been performed via a variety of methods including: maleimide linkage, disulfide linkage, click chemistry, or amide linkage between the free PMO secondary amine and an activated carboxylic group at the c-terminus of the peptide, which is the most popular [21]. Initial reports showing promising results using this chemistry were based on using arginine-rich peptides together with other chemical modifications such as aminohexanoic acid and beta alanine [44,45].…”
Section: Covalent Conjugation Approach For Nucleic Acid Delivery Withmentioning
confidence: 98%
“…Importantly, they demonstrate excellent potential for the delivery of nucleic acids, ranging from natural or synthetic short RNA or DNA ONs to much larger plasmid molecules, both in vitro and in vivo [19][20][21][22]. CPPs can have very different origin and are in many ways ambiguous to define.…”
Section: Introductionmentioning
confidence: 99%
“…Among them, arginine-rich CPPs such as Tat peptide from a human immunodeficiency virus (HIV)-1 trans-activator protein TAT, [1][2][3] Penetratin peptide from a Drosophila homeodomain Antennapedia 4,5) and oligoarginines 6,7) show high efficiency of internalization, facilitating intracellular delivery of a wide range of hydrophilic molecules including small compounds, peptides, proteins, nucleic acids, nanoparticles, liposomes, and others that would be otherwise difficult to enter cells. [8][9][10] Arginine-rich CPPs have, therefore, attracted much attention as one of the promising carriers for intracellular delivery of therapeutic molecules including nucleic acids and drug candidates. [8][9][10] So far, a number of peptide sequences have been reported as CPPs, which are classified by their physicochemical characteristics, such as basic/amphiphilic CPPs that contain several basic amino acids including arginine and lysine, and hydrophobic CPPs (Table 1): interestingly, polyhistidine peptide such as histidine 16-mer (H16) is recently reported as CPPs.…”
Section: Introductionmentioning
confidence: 99%
“…[8][9][10] Arginine-rich CPPs have, therefore, attracted much attention as one of the promising carriers for intracellular delivery of therapeutic molecules including nucleic acids and drug candidates. [8][9][10] So far, a number of peptide sequences have been reported as CPPs, which are classified by their physicochemical characteristics, such as basic/amphiphilic CPPs that contain several basic amino acids including arginine and lysine, and hydrophobic CPPs (Table 1): interestingly, polyhistidine peptide such as histidine 16-mer (H16) is recently reported as CPPs. 11) Although the molecular mechanisms as to how argininerich CPPs enter cells have not been fully understood and still remain debated, it is commonly accepted that internalization of these peptides involves endocytosis.…”
Section: Introductionmentioning
confidence: 99%
“…However, clinical use of these agents would require circumvention of the challenges relating to their appropriate design, higher biological stability and targeted delivery. Various in vitro studies have revealed increase in cellular uptake of these agents by employing a delivery system [32][33][34] . However, delivery strategies need to be more refined and in vivo studies needs to be employed to evaluate the safety and toxicity associated with the delivery system 33 .…”
Section: Resultsmentioning
confidence: 99%